2019
DOI: 10.7759/cureus.5883
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Knee Hemarthrosis Due to Hypofibrinogenemia Following Tigecycline Treatment for Periprosthetic Joint Infection

Abstract: Tigecycline, a recently approved antibiotic, has a broad spectrum of antimicrobial activity. Its unique structure and properties make tigecycline a valuable option for the treatment of infections caused by many multidrug-resistant organisms. We present a case of an 82-year-old patient who developed a significant decrease of fibrinogen levels after the addition of tigecycline to his antibiotic regimen. The patient was treated for a periprosthetic knee joint infection caused by a multidrug-resistant extended-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Tigecycline-associated hypofibrinogenemia was first reported in a case study by Pieringer et al in 2010, which is currently a documented adverse event ( Pieringer et al, 2010 ). A retrospective study in China found a decrease in fibrinogen in patients treated with tigecycline ( Zhang et al, 2015 ) and several cases of potentially life-threatening coagulation disorders induced by tigecycline have also been reported ( Akalay et al, 2021 ; Balfousias et al, 2019 ; Fan et al, 2020 ; Rossitto et al, 2014 ; Routsi et al, 2015 ; Sabanis et al, 2015 ; Wu et al, 2017 ; Yılmaz Duran et al, 2018 ). However, although various reports have demonstrated an association between tigecycline and hypofibrinogenemia, the findings could not provide practical reference for clinical administration of tigecycline due to limitations such as small sample sizes, lack of a control group and insufficient description.…”
Section: Introductionmentioning
confidence: 99%
“…Tigecycline-associated hypofibrinogenemia was first reported in a case study by Pieringer et al in 2010, which is currently a documented adverse event ( Pieringer et al, 2010 ). A retrospective study in China found a decrease in fibrinogen in patients treated with tigecycline ( Zhang et al, 2015 ) and several cases of potentially life-threatening coagulation disorders induced by tigecycline have also been reported ( Akalay et al, 2021 ; Balfousias et al, 2019 ; Fan et al, 2020 ; Rossitto et al, 2014 ; Routsi et al, 2015 ; Sabanis et al, 2015 ; Wu et al, 2017 ; Yılmaz Duran et al, 2018 ). However, although various reports have demonstrated an association between tigecycline and hypofibrinogenemia, the findings could not provide practical reference for clinical administration of tigecycline due to limitations such as small sample sizes, lack of a control group and insufficient description.…”
Section: Introductionmentioning
confidence: 99%
“…Campany-Herrero et al found that high-dose tigecycline treatment and treatment duration >4 weeks were risk factors for a reduction in fibrinogen plasma concentration >1.7 g/L (16). As previously reported, tigecycline-associated hypofibrinogenemia is reversible and the FIB level normalizes within days of tigecycline discontinuation (30).…”
Section: Discussionmentioning
confidence: 80%